Assessing The Role of Technology Advancement in Improving Women’s Participation in The Digital Economy in Kampala Metropolitan, Uganda - Elizabeth Naume; Kafeero Kiggundu (Universitas Pembangunan Nasional Veteran Jakarta, 2026)
This study assessed the role of technology advancement in improving women’s participation in the digital economy within the Kampala Metropolitan area. It employs a combination of descriptive, cross sectional survey design, the research integrated both quantitative data from surveys and qualitative insights from interviews with women and relevant stakeholder, including technology trainers and government stakeholders. The target population consisted of approximately 500 women in the Kampala Metropolitan area, with a calculated sample size of 222 participants based on Slovin’s formula and a 5% margin of error. The findings expressed that technology advancement significantly influence women’s participation in the digital economy with an R2 value of 0.413 indicating that about 41.3% of the variation in participation could be as a result to technology advancement. The regression analysis indicated a strong positive effect (B=0.587, B =0.643, t=8.291, p<0.001), confirming the statistical significance of the relationship. ANOVA results further validated the model’s robustness (F-statistic=68.753, p<0.001). These results highlighted that enhanced access to digital tools and platforms was crucial for empowering women financially. The study concludes that technology advancements had positively impacted women economically. The study concluded that technology advancements had positively impacted women’s participation by creating an enabling environment for them to engage in online transactions and manage businesses with greater freedom and control. Recommendations included the development of gender responsive digital policies aimed at reducing financial barriers, such as subsidized internet rates and increased accessed access to affordable digital devices. By fostering these initiatives, stakeholders could significantly enhance women’s involvement in the digital economy. promoting inclusive economic development. Keywords : Technology advancement; Women’s participation; Digital Economy; Kampala Metropolitan; Uganda, Gender responsive policies. Abstrak Studi ini menilai peran kemajuan teknologi dalam meningkatkan partisipasi perempuan dalam ekonomi digital di wilayah Metropolitan Kampala. Ini menggunakan kombinasi desain survei deskriptif dan crosssectional, penelitian ini mengintegrasikan data kuantitatif dari survei dan wawasan kualitatif dari wawancara dengan perempuan dan pemangku kepentingan yang relevan, termasuk pelatih teknologi dan pemangku kepentingan pemerintah. Populasi target terdiri dari sekitar 500 wanita di wilayah Metropolitan Kampala, dengan ukuran sampel yang dihitung sebesar 222 peserta berdasarkan rumus Slovin dan margin kesalahan 5%. Temuan tersebut mengungkapkan bahwa kemajuan teknologi secara signifikan mempengaruhi partisipasi perempuan dalam ekonomi digital dengan nilai R2 0,413 yang menunjukkan bahwa sekitar 41,3% variasi partisipasi dapat disebabkan oleh kemajuan teknologi. Analisis regresi menunjukkan efek positif yang kuat (B = 0,587, B = 0,643, t = 8,291, p<0,001), mengkonfirmasi signifikansi statistik dari hubungan tersebut. Hasil ANOVA lebih lanjut memvalidasi ketahanan model (F-statistik = 68,753, p<0,001). Hasil ini menyoroti bahwa peningkatan akses ke alat dan platform digital sangat penting untuk memberdayakan perempuan secara finansial. Studi ini menyimpulkan bahwa kemajuan teknologi telah berdampak positif pada perempuan secara ekonomi. Studi ini menyimpulkan bahwa kemajuan teknologi telah berdampak positif pada partisipasi perempuan dengan menciptakan lingkungan yang memungkinkan bagi mereka untuk terlibat dalam transaksi online dan mengelola bisnis dengan kebebasan dan kontrol yang lebih besar. Rekomendasi termasuk pengembangan kebijakan digital responsif gender yang bertujuan untuk mengurangi hambatan keuangan, seperti tarif internet bersubsidi dan peningkatan akses akses ke perangkat digital yang terjangkau. Dengan mendorong inisiatif ini, para pemangku kepentingan dapat secara signifikan meningkatkan keterlibatan perempuan dalam ekonomi digital. mempromosikan pembangunan ekonomi inklusif. Keywords : Kemajuan teknologi; Partisipasi perempuan; Ekonomi Digital; Metropolitan Kampala; Uganda, Kebijakan responsif gender.